Phytosterol supplementation in the treatment of dyslipidemia in children and adolescents: a systematic review - Mantovani,Luisa Montone (2021)
ABSTRACT Objective: To carry out a systematic review on the effects of phytosterol supplementation on the treatment of dyslipidemia in children and adolescents. Data sources: Review in the SciELO, Lilacs, Bireme, PubMed and Web of Science databases, with no time limit. Descriptors: phytosterols or plant sterols and dyslipidemias, hypercholesterolemia, cholesterol, children, adolescent, in English and Portuguese. The articles included were published in Portuguese, English or Spanish and evaluated the effect of phytosterol supplementation in pediatric patients with dyslipidemia. Documents that involved adults or animals, review papers, case studies and abstracts were excluded. Two authors performed independent extraction of articles. Of 113 abstracts, 19 were read in full and 12 were used in this manuscript. Data synthesis: Phytosterol supplementation to reduce cholesterol levels has been shown to be effective in reducing LDL-cholesterol levels by approximately 10%, with reductions above 10% in LDL-cholesterol levels observed after 8 to 12 weeks of intervention. Studies have not shown significant changes in HDL-cholesterol and triglyceride levels. Based on the absence of adverse effects, its use seems to be safe and of good tolerance in children and adolescents. Conclusions: Phytosterol supplementation seems to be of great therapeutic aid for the treatment of hypercholesterolemia in children and adolescents. Further studies assessing the long-term effect of phytosterol supplementation are necessary.